Embedded iron object detection using asynchronous full wave envelope detector technique in ground penetrating radar system - Maryanti Razali; Ariffuddin Joret; Muhammad Suhaimi Sulong; Mohammad Faiz Liew Abdullah; Elfarizanis Baharudin; Che Ku Nor Azie Hailma Che Ku Melor; Nur Izzati Zulkefli; Noor Azwan Shairi (Institute of Advanced Engineering and Science, 2022)
The use of a ground penetrating radar (GPR) system that operates at low frequencies allows the detection of embedded objects underground from the earth’s surface deeper than high frequency. However, the output signal generated from the system using pulse modulation (PM) technique and high-frequency carrier, has many high ripple signals consequently resulting in a blurry image. Nevertheless, this ripple signal can be minimized by reprocessing the signal using an envelope detector method. In this study, an envelope detection technique called ArJED© asynchronous full-wave (AFW) was used in the GPR system and was tested at a frequency range from 0.06 to 0.08 GHz. A dipole antenna has been used as an embedded object detection sensor of the GPR system. The detection system of embedded objects involves four depths starting with 2 cm depth, 5 cm, 7 cm, and 20 cm. A comparison of embedded object images before and after the application of the envelope detection technique was done and proved that the proposed envelope detection technique has produced a clearer radargram image of the GPR system.